2005
DOI: 10.1300/j233v04n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Pathways to Diffusion of Methamphetamine Use Among African Americans in the Rural South

Abstract: There are no studies of African Americans methamphetamine use in the South where it is widespread among whites. We describe factors that inhibit or facilitate the diffusion of methamphetamine use among African Americans based on qualitative interviews with 86 drug users in rural Arkansas and Kentucky. Results suggest low prevalence of methamphetamine use among African Americans, and interviewees cited several barriers to its diffusion which were linked to the drug's ingredients, psychoactive and physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Black adolescents were significantly less likely than white adolescents to use methamphetamine in the past year, but this relationship disappeared in the model of past-year nonmedical use of prescription stimulants. Ethnographic studies suggest that white individuals are more likely to report methamphetamine use, whereas black individuals are more likely to report crack use, largely due to characteristics of the production, distribution, and social ecologies of these drugs [26]. Additionally, Hispanic ethnicity was linked with reduced odds of past-year nonmedical use of prescription stimulants only.…”
Section: Discussionmentioning
confidence: 98%
“…Black adolescents were significantly less likely than white adolescents to use methamphetamine in the past year, but this relationship disappeared in the model of past-year nonmedical use of prescription stimulants. Ethnographic studies suggest that white individuals are more likely to report methamphetamine use, whereas black individuals are more likely to report crack use, largely due to characteristics of the production, distribution, and social ecologies of these drugs [26]. Additionally, Hispanic ethnicity was linked with reduced odds of past-year nonmedical use of prescription stimulants only.…”
Section: Discussionmentioning
confidence: 98%
“…Other research based on nationally representative data from the 2002 National Survey of Drug Use and Health has also found black youths to be less likely to use methamphetamine than white and Hispanic youths (Wu et al, 2006). Ethnographic research has identified several barriers to the diffusion of methamphetamine use in the African American community, including difficulty in accessing distribution networks, the drug's ingredients and effects, and African American preference for cocaine (Sexton et al, 2005). Research on the opportunity to use hallucinogens may shed further insights on ethnic differences found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research suggests that many rural stimulant users avoid treatment because of concerns about remaining anonymous (Sexton et al, 2005) and quantitative research indicates that rural at-risk drinkers are more likely than their urban counterparts to express concerns about treatment privacy (Fortney et al, 2004). We found no relationship between related stigma constructs, secrecy and perceived devaluation, and preferred treatment site.…”
Section: Discussionmentioning
confidence: 99%
“…Many rural drug users might prefer to seek treatment outside of their home town simply to avoid the risk of being seen walking through the door of a local treatment center. In a qualitative study of rural stimulant users, one participant summed up the sentiment in this way, “I wouldn’t want to do it, because the whole town would be talking about it”(Sexton et al, 2005) (p. 125). Moreover, from the broader substance use literature, a multi-state study of at-risk drinkers showed that those residing in rural areas were more likely than urban dwellers to report a lack of privacy when accessing local alcohol treatment services (Fortney et al, 2004).…”
Section: Introductionmentioning
confidence: 99%